High‐Grade Prostatic Intraepithelial Neoplasia (HGPIN) and topographical distribution in 1, 374 prostatectomy specimens: Existence of HGPIN near prostate cancer12. Issue 10 (26th March 2013) - Eminaga, Okyaz; Hinkelammert, Reemt; Abbas, Mahmoud; Titze, Ulf; Eltze, Elke; Bettendorf, Olaf; Semjonow, Axel
Abstract PURPOSE High‐grade prostatic intraepithelial neoplasia (HGPIN) is believed to be a precursor of prostate cancer (PCa). This study evaluated whether HGPIN was located close to PCa in whole radical prostatectomy specimens (RPSs). MATERIALS AND METHODS We evaluated 1, 374 prostate specimens from 1999 to 2010 using a cMDX‐based map model of the prostate. The distribution of 10, 439 PCa foci was analyzed and visualized on a heat map. The color gradient of the heat map was reduced to six colors representing the frequency classification of the relative frequency of PCa using an image posterization effect. We defined 22 regions in the prostate according to the frequency of PCa occurrence. Seven hundred ninety RPSs containing 6, 374 PCa foci and 4, 502 HGPIN foci were evaluated. The topographical association between PCa and HGPIN in the RPSs was analyzed by estimating the frequencies of PCa and HGPIN in 22 regions. A logistic regression analysis was performed to assess the odds ratios of HGPIN for the presence of PCa in 22 regions. RESULTS Fifty‐eight percent of PCa specimens included HGPIN and had significantly more favorable Gleason scores, lower PSA levels and smaller relative tumor volumes than isolated PCa specimens. HGPIN (68%) and PCa (69%) were predominantly localized to the apical half of the prostate. HGPIN was mainly concentrated in the peripheral zone medial to regions with high PCa frequencies. Upon logistic regression analysis, HGPIN was a significant predictor of PCa co‐existence in 11 regions. CONCLUSIONS HGPIN was located adjacent to PCa in whole RPSs. PCa concomitant with HGPIN had more favorable pathologic features than isolated PCa. Prostate 73: 1115–1122, 2013. © 2013 Wiley Periodicals, Inc.